Magnetooptic coupling coefficients for one- and two-magnon Raman scattering in the rutile-structure antiferromagnets FeF₂, MnF₂, CoF₂ and NiF₂ - Lockwood, D.J.; Cottam, M.G. (Физика низких температур, 2012)
Inelastic light scattering intensities of magnetic excitations are governed by the magnetooptic coupling coefficients,
which have been evaluated, for example, for the ferrimagnet Y₃Fe₅O₁₂ (YIG) and the metamagnets
FeC₁₂ and FeBr₂. However, by far the most detailed studies to date have been performed on the classic rutilestructure
antiferromagnets, and we summarize here the results obtained from the many experimental and theoretical
investigations in these compounds for both one-magnon and two-magnon excitations. A comparison of the
magnitudes of the various coupling coefficients for MnF₂, FeF₂, CoF₂, and NiF₂ reveals a surprising similarity
in many coefficients. In one-magnon Raman scattering, the in-phase linear magnetooptic coefficient dominates
and the main differences between MnF₂, FeF₂, and NiF₂ lie in the relative significance of the in-phase quadratic
magnetooptic coefficient. Thus the quadratic coefficients are now seen to be of particular importance in determining
the strength of the one-magnon scattering in a variety of magnetic insulators. In two-magnon Raman
scattering, one magnetooptic coefficient dominates for all of these antiferromagnets. However, each of the other
six coefficients are remarkably similar in magnitude, in general, and not negligible in most cases, indicating
some universality in the way light interacts with the pairs of magnons of opposite and equal wave vector in rutile
structure antiferromagnets.